Ion channels in sulfonated copolymer-grafted nanoparticles in ionic liquids. Issue 29 (11th July 2022) - Li, Ruhao; Han, Yuke; Akcora, Pinar
Abstract : Poly(methyl methacrylate)- b -poly(styrene sulfonate) (PMMA- b -PSS) copolymer-grafted Fe3 O4 nanoparticles with different sulfonation levels exhibited concentration dependent ionic conductivities in acetonitrile and HMIm–TFSI/acetonitrile mixtures. Abstract : The use of ionic liquids as solvents for polymers or polymer-grafted nanoparticles provides an exciting feature to explore electrolyte–polymer interactions. 1-Hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (HMIm–TFSI) can have specific interactions with the polymer through ion-dipole forces or hydrogen bonding. In this work, poly(methyl methacrylate)- b -poly(styrene sulfonate) (PMMA- b -PSS) copolymer-grafted Fe3 O4 nanoparticles with different sulfonation levels (∼4.9 to 10.9 mol% SS) were synthesized, and their concentration dependent ionic conductivities were reported in acetonitrile and HMIm–TFSI/acetonitrile mixtures. We found that conductivity enhancement with the particle concentration in acetonitrile was due to the aggregation of grafted particles, resulting in sulfonic domain connectivity. The ionic conductivity was found to be related to the effective hopping transfer within ionic channels. On the contrary, the conductivity decreased or remained constant with increasing particle concentration in HMIm–TFSI/acetonitrile. This result was attributed to the ion coupling between ionic liquids and copolymer domains.